The evolution of epistemological methodologies in anatomy: From antiquity to modern times. Issue 4 (24th September 2021) - Ghosh, Sanjib Kumar
Abstract: Present day scenario regarding epistemological methods in anatomy is in sharp contrast to the situation during ancient period. This study aimed to explore the evolution of epistemological methodologies in anatomy across centuries. In ancient times Egyptian embalmers acquired anatomical knowledge from handling human bodies and likewise anatomical studies in India involved human dissection. Ancient Greeks used theological principles‐based methods, animal dissection and human dissection in practice of anatomy. Human dissection was also practiced in ancient China for gaining anatomical knowledge. Prohibition of human dissection led to use of animal dissection in ancient Rome and the trend continued in Europe through Middle Ages. Epistemological methods used by Muslim scholars during Middle Ages are not clearly chronicled. Human dissection returned as primary epistemological method in Renaissance Europe and empirical methods were reinstated after ancient period in human dissection during 16th century. The situation further improved with introduction of pragmatic experiment based approach during 17th century and autopsy‐based methods during 18th century. Advances in anatomical knowledge continued with advent of microscope‐based methods and emergence of anatomical sections in practice of human dissection in 19th century. Introduction of human observational studies, medical imaging, and molecular methods presented more options in terms of epistemological methods for investigating the human body during 20th century. Onset of 21st century has witnessed dominance of technology‐based methods in anatomy. Limited emphasis on ethics in epistemological methodologies since antiquity is a dark aspect of otherwise an eventful evolutionary journey but recent developments are in positive direction.